Deciphering the therapeutic effects of Xiyanping injection: insights into pulmonary and gut microbiome modulation, SerpinB2/PAI-2 targeting, and alleviation of influenza a virus-induced lung injury - Tengwen Liu; Shuping Li; Xuerui Wang; Mingjiang Liu; Yuchen Wang; Jie Ying; Shuwen Zhang; Yan Lin; Ning Wang; Yungjing Bai; Lan Xie; Tengfei Chen; et al. (Virology Journal)
Abstract Infection with Influenza A virus (IAV) induces severe inflammatory responses and lung injury, contributing significantly to mortality and morbidity rates. Alterations in the microbial composition of the lungs and intestinal tract resulting from infection could influence disease progression and treatment outcomes. Xiyanping (XYP) injection has demonstrated efficacy in clinical treatment across various viral infections. However, its specific effects and mechanisms against IAV remain unclear. In this study, we established an IAV infection mice model, and utilized 16 S rRNA sequencing, RNA sequencing, protein chips, and molecular docking, to investigate the mechanisms of XYP injection on altering pulmonary and gut microbiota, and identifying its target sites. We revealed that XYP injection significantly reduced mortality, weight loss, lung viral titers, and lung pathology in IAV-infected mice. XYP injection down-regulated the activity of malondialdehyde, and the levels of interleukin (IL)-1β, IL-5, IL-6, tumor necrosis factor-α, IL-18, IL-15, granulocyte colony-stimulating factor, IL-9, chemokine (C-C motif) ligand-5, and C-X-C motif chemokine ligand 5, while up-regulated the activities of glutathione peroxidase reactive and superoxide dismutase, and the level of interferon-γ. The diversity of the pulmonary and gut microbiota was altered slightly after XYP injection. The linear discriminant analysis of the gut microbes revealed a higher proportion of potentially beneficial bacteria, including Akkermansia, Parabacteroides goldsteinii, Defluviitaleaceae, Oscillospirales, and Eubacterium_coprostanoligenes_group characterized the XYP group. Peritoneal macrophage RNA sequencing highlighted Serpinb2 as the most significantly regulated gene by XYP injection, along with consistent changes in multiple downstream Th2 structure genes. KEGG pathway analysis indicated significant modifications in genes associated with influenza A, mitogen-activated protein kinase signaling, nuclear factor kappa-B signaling, and apoptosis following XYP injection. Finally, human protein chips and molecular docking were carried out to confirm the binding of the main component of XYP injection, andrographolide, with SERPINB2/PAI-2 protein. Overall, our study provides valuable insights into the therapeutic potential of XYP injection in treating influenza, highlighting its multifaceted effects on host microbiota and immune responses, and pinpointing SerpinB2/PAI-2 as the target for XYP injection in exerting anti-inflammatory and antiviral therapeutic mechanisms.